1995
DOI: 10.1068/p241297
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Gaze Direction: A Stare-In-The-Crowd Effect

Abstract: A visual-search paradigm was used to explore the relative ease with which the direction of gaze can be detected. Straight-gaze stimuli were presented as targets within a variable number of distractors with left-averted or right-averted gaze. Reaction time in this case was compared with that when either the left-averted or right-averted gaze stimuli were the targets among distractors of the two remaining gaze directions. The data were examined for the existence of a search asymmetry favoring the straight-gaze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
183
5
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(225 citation statements)
references
References 28 publications
28
183
5
3
Order By: Relevance
“…Their findings, which may indicate the delayed development of gaze processing in autism, are intriguing. But it is surprising they did not find any gazedirection effect in non-autistic participants, considering the sensitivity to the perceived eye gaze direction often found in other behavioral studies (e.g., Senju & Hasegawa, in press;von Grünau & Anston, 1995). It might be due to the use of passive viewing paradigm, rather than active detection or discrimination tasks usually used in behavioral studies.…”
Section: Introductionmentioning
confidence: 56%
“…Their findings, which may indicate the delayed development of gaze processing in autism, are intriguing. But it is surprising they did not find any gazedirection effect in non-autistic participants, considering the sensitivity to the perceived eye gaze direction often found in other behavioral studies (e.g., Senju & Hasegawa, in press;von Grünau & Anston, 1995). It might be due to the use of passive viewing paradigm, rather than active detection or discrimination tasks usually used in behavioral studies.…”
Section: Introductionmentioning
confidence: 56%
“…Mutual eye gaze, in particular, serves to signal the likely flavor of a social interaction, be it nasty or nice, to initiate and regulate social communication, and to provide important information about the mental states of others (Nummenmaa & Calder, 2009). It is perhaps of no surprise, then, that adults are exquisitely sensitive to gaze direction (von Grünau & Anston, 1995), that such sensitivity emerges early in ontogenesis (Farroni, Mansfield, Lai, & Johnson, 2003), and that atypicalities in gaze processing are a defining feature of autism (American Psychiatric Association [APA], 2000), a developmental condition characterized by profound difficulties in social reciprocity and communication.…”
mentioning
confidence: 99%
“…For example, in a visual search task, a straight gaze direction among averted gaze directions is detected faster and with fewer errors than is an averted gaze among straight gaze directions (von Grünau & Anston, 1995). Until now, numerous studies have investigated how observers know where another person is looking (e.g., Anstis, Mayhew, & Morley, 1969;Cline, 1967;Gibson & Pick, 1963;Symons, Lee, Cedrone, & Nishimura, 2004;Todorović, 2006) and have demonstrated that observers discriminate the gaze direction of another person with high accuracy.…”
mentioning
confidence: 99%